RANCANG BANGUN APLIKASI PENENTUAN PERSEDIAAN BERDASARKAN PERAMALAN PENJUALAN PADA CV. AGUNG JAYA CABANG PABEAN - Juli Tridantono; Sulistiowati Sulistiowati; Julianto Lemantara (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
CV. Agung Jaya Branch Customs is a distributor of office stationery and various plastics. In the determination of inventory, the company is not using the method. The number of competition raises the sales volume is not stable, especially a variety of plastic products. Result in the accumulation of stock in warehouse and other stocks due to insufficient, thus making customers switch to other distributors.Winters exponential smoothing method is used as a forecasting method, is based on the analysis of the data pattern of plastic products that contain the data pattern trend and seasonal elements. MAPE is used to measure the degree of forecasting error. The author uses the method of PRS (Periodic Review System) to determine the order quantity 1 month to come based on forecasting data, review stock last and maximum inventory.Applications are designed and built to help the general manager CV. Agung Jaya Customs branch in decision support for inventory after knowing the sales forecast in the future. Demand can always be met and the application is designed and constructed to reduce the accumulation of stock in warehouse. Seen on Plastic Glasses 12 with MAPE 0,025. Plastic cups 14 to 0,020 MAPE. Aqua Plastic cups with MAPE 0,025. Plastic Ice cream cups with MAPE 0.089. Plastic bag No. 15 with 0,165 MAPE. Plastic bag No. 21 with a 0.070 MAPE. Plastic bag No. 28 with 0.175 MAPE. Plastic bag No. 35 with 0,002 MAPE. Plastic bag No. 40 with 0,013 MAPE. Transparent Plastic 1 Kg with MAPE 0.01.